Relationship Between Vapour Pressure and Evaporation from U.S.D.A. Type 1 Pan Located at Bamrauli (Allahabad) - Sirothia, N.N; Singh, Jaswant (Journal of Soil and Water Conservation, 2022)
Evaporation is defined as the natural process by which any form of water, liquid or solid, is changed into vapour Houk (1960).The loss of water due to evaporation is an important factor for water storage in sub humid and arid regions. It affects the water storage capacity of hydroelectric and irrigation projects in arid regions. It is of great benefit to agricultural engineers in assessing the irrigation needs, and planning of irrigation systems.Evaporation is a function of temperature, vapour pressure, wind velocity, atmospheric pressure and properties of water. An accurate quantitative evaluation of realative effectiveness of each is difficult because of their interdependence and complex nature of the problem. Out of these vapour pressure is the main variable affecting evaporation. The magnitude of vapour pressure depends on the percentage saturation of the air. Accor-dingly vapour pressure is measured (i) when the atmosphere is unsaturated (va ). and (ii) the corresponding value of the air is fully saturated (vs ).